The Role of Additives in Suppressing the Degradation of Liquid‐Exfoliated WS2 Monolayers. Issue 42 (3rd September 2021) - Karger, Leonhard; Synnatschke, Kevin; Settele, Simon; Hofstetter, Yvonne J.; Nowack, Tim; Zaumseil, Jana; Vaynzof, Yana; Backes, Claudia
Abstract: Group VI transition metal dichalcogenides (TMDs) are considered to be chemically widely inert, but recent reports point toward an oxidation of monolayered sheets in ambient conditions, due to defects. To date, the degradation of monolayered TMDs is only studied on individual, substrate‐supported nanosheets with varying defect type and concentration, strain, and in an inhomogeneous environment. Here, degradation kinetics of WS2 nanosheet ensembles in the liquid phase are investigated through photoluminescence measurements, which selectively probe the monolayers. Monolayer‐enriched WS2 dispersions are produced with varying lateral sizes in the two common surfactant stabilizers sodium cholate (SC) and sodium dodecyl sulfate (SDS). Well‐defined degradation kinetics are observed, which enable the determination of activation energies of the degradation and decouple photoinduced and thermal degradation. The thermal degradation is slower than the photoinduced degradation and requires higher activation energy. Using SC as surfactant, it is sufficiently suppressed. The photoinduced degradation can be widely prevented through chemical passivation achieved through the addition of cysteine which, on the one hand, coordinates to defects on the nanosheets and, on the other hand, stabilizes oxides on the surface, which shield the nanosheets from further degradation. Abstract : The degradation of liquid‐exfoliated WS2 monolayers is studied in situ through photoluminescence as function of time and temperature in two surfactant systems (sodium cholate—SC; sodium dodecyl sulfate—SDS). The kinetics reveal that a photoinduced degradation (activation energy ≈25 kJ mol −1 ) is dominant in SC, while an additional thermal degradation (activation energy ≈50 kJ mol −1 ) is observed in SDS.